Designing Website-Based Scholarship Management Application for Teaching of Analytical Hierarchy Process (AHP) in Decision Support Systems (DSS) Subjects - Tasrif, Elfi; Saputra, Hadi Kurnia; Kurniadi, Denny; Hidayat, Hendra; Mubai, Akrimullah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Teaching Analytical Hierarchy Process (AHP) in Decision Support Systems (DSS) subjects encourages students to know how a good decision is taken. AHP itself in the field of education and teaching has been widely used as an effective and efficient method in solving educational problems. The purpose of this paper is to designing website-based scholarship management application for teaching of Analytical Hierarchy Process (AHP) in Decision Support Systems (DSS) subjects. Scholarship management using AHP is choosing the right criteria is very important. This system uses 5 criteria, namely academic value, academic achievement, non-academic achievement, parents 'income, and parents' dependents, as a basis for producing decision-supporting information. The scholarship management system is embodied in a website-based computer application. Utilizing this application provides more assistance to donors, so that the results of this learning are not only proven in theory but also in practice in real conditions. In addition, the Website-Based Scholarship Management Application can be run on a mobile basis and can be accessed wherever and whenever they are.